Graft failure after reduced-intensity stem cell transplantation for congenital sideroblastic anemia. (2nd January 2019) - Imataki, Osamu; Uchida, Shumpei; Uemura, Makiko; Kadowaki, Norimitsu
Abstract: Congenital sideroblastic anemia (CSA) is a rare hereditary disease causing disorders of hemoglobin synthesis. Severe, progressive congenital sideroblastic anemia becomes transfusion dependent and results in iron overload. In such cases, patients must undergo stem cell transplantation (SCT) before critical organ dysfunction occurs. However, there has been no consensus on the criteria for SCT for congenital sideroblastic anemia. A 17-year-old Japanese boy was newly diagnosed with congenital sideroblastic anemia manifesting dyspnea on effort. His gene analysis revealed ALAS2 R170L. He gradually become dependent on RBC transfusion. Vitamin B6 (pyridoxal, 30 mg/day) therapy and high-dose alpha-linoleic acid supplementation (150 mg/day) had not been effective. We treated the patient with reduced-intensity SCT from a human leukocyte antigen (HLA) alle 8/8-identical unrelated female donor. The preparation regimen applied consisted of cyclophosphamide, fludarabine, total body irradiation (2 Gy), and anti-thymocyte globulin. We experienced secondary graft failure, nevertheless we used enough immunosuppression. Here we discuss the optimal transplantation regimen for an adult-onset congenital sideroblastic anemia patient with transfusion dependency and mild hemosiderosis. We consider a positive indication for SCT in younger (< 20-year-old) patients with congenital sideroblastic anemia with transfusion dependency. Each case should be individually considered for their suitability for SCT depending on the feasibility and the clinical condition of the patient.